Efficacy of SG Shield in reducing droplet contamination during collection of oropharyngeal swab culture specimens - Phui-Sze Angie Au-Yong; Xuanxuan Chen; Wen Hao Low; Keen Chong Chau; Stephanie Fook-Chong; Shariq Ali Khan (Singapore Medical Journal)
Introduction: Oropharyngeal swabs for diagnosis of COVID-19 often induce violent coughing, which can disperse infectious droplets onto providers. Incorrectly doffing personal protective equipment (PPE) increases the risk of transmission. A cheap, single-use variation of the face shield invented by a Singaporean team, SG Shield, aims to reduce this risk. This manikin study aimed to study the efficacy of the SG Shield in combination with standard PPE. Methods: A person attired in full PPE whose face and chest was lined with grid paper stood in front of an airway manikin in an enclosed room. A small latex balloon containing ultraviolet fluorescent dye was placed in the oral cavity of the manikin and inflated until explosion to simulate a cough. Three study groups were tested: (a) control (no shield), (b) face shield and (c) SG Shield. The primary outcome was droplet dispersion, determined quantitatively by calculating the proportion of grid paper wall squares stained with fluorescent dye. The secondary outcome was the severity of provider contamination. Results: The SG Shield significantly reduced droplet dispersion to 0% compared to the controls (99.0%, P = 0.001). The face shield also significantly reduced droplet contamination but to a lesser extent (80.0%) compared to the control group (P = 0.001). Although the qualitative severity of droplet contamination was significantly lower in both groups compared to the controls, the face shield group had more contamination of the provider’s head and neck. Conclusion: The manikin study showed that the SG Shield significantly reduces droplet dispersion to the swab provider’s face and chest.